Efektivitas Pemberian Bantuan Hukum terhadap Tersangka yang Tidak Mampu pada Tingkat Penyidikan: Studi Kasus di Polresta Banyumas - Martinus Prima Hasiholan Turnip; Angkasa; Budiyono (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Martinus Prima Hasiholan Turnip, Master of Law Study Program, Postgraduate Program, Jenderal Soedirman University, "The Effectiveness of Providing Legal Aid to Suspects Who Are Unable to Afford It at the Investigation Level at the Banyumas Police" Supervisory Commission, Prof. Dr. Angkasa, S.H., M.Hum. Member, Dr. Budiyono, S.H., M.Hum. This study aims to determine the effectiveness and factors that are inhibiting the effectiveness of providing legal aid to suspects who are unable to afford it at the investigation level at the Banyumas Police Sociological juridical approach, descriptive, Research Location at the Banyumas Police. Primary data collection with interviews, secondary data from literature studies. The data is presented in the form of descriptions, analyzed qualitatively. Based on the results of the research and discussion, it can be concluded as follows: the basis for providing legal aid is regulated in Article 28 paragraph (1) of the 1945 Constitution, Article 56 of the Criminal Procedure Code, and Law Number 16 of 2011 concerning Legal Aid that at the beginning of the examination process, the investigator is obliged to notify the suspect of the right to legal aid, but in practice,  There are still suspects who are unable to afford to be unaware of the existence of free legal aid so that the implementation is not effective. In the process of implementation, the inhibiting factors that occurred included in terms of legal structure, substance and culture.